Search of Emergency Foods through Wild Flora of Jammu and Kashmir State: Sunderbani Area-I - Atal, C. K.; Sharma, B. M.; Bhatt, A. K. (Indian Forester, 1980)
Strategic situativon of Jammu and Kashmir State alls for a knowledge of its wild flora which could be used as source of food under conditions of emergency. Areas in and around the border town of sunderbani have been surveyed for such plants and potentiality of latter in the above respect has been discussed. Descriative comments and illustrations have been furnished to facilitate the diagnosis of Pueraria tuberosa C.tuberulala Dioscoreas belophylla and D.bulbifera in field. C.tuberoulala is unsuitable on account of its unique shape P.tuberosa possesses much swollen tubers rarely also the roots acquiring the appearance of headed strings of D.bulbifera and D.belophylla can be distinguished from each other by their specific direction of twining. From other twiners in the area they can be distinguished by the presence of bulbifera. Distribution of these four species has been recorded and their conventional modes of consumption examiend pueraria tubers can be consumed even without cooking whereas D.belophylla tubers and curalluma can be eaten after cooking in ordinary way. D.bulbifera needs Some preparation prior to consumption. Chemical analysis shows curalluma to be a rich source of Vitamin C, calcium and iron, Dioscoreas compare favourably with potato, sweet potato and tapioca in starch content,pueraria is a moderate source of calcium, iron and carbohydrates.